Retrocaval Ureter Manifested after Ureteral Reimplantation for Ipsilateral Vesicoureteral Reflux: A Case Report - Katsui, Masahiro; Asanuma, Hiroshi; Fukumoto, Keishiro; Mizuno, Ryuichi; Oya, Mototsugu (Urology Journal, 2018)
We report a female patient diagnosed with retrocaval ureter (RCU) after ureteral reimplantation for vesicoureteral reflux (VUR). She was diagnosed as right grade IV VUR with breakthrough urinary tract infections, and underwent ureteral reimplantation with Cohen cross-trigonal technique. Thereafter, she developed severe right hydronephrosis associated with RCU, which was presumably due to caudal traction of right ureter at ureteral reimplantation. She underwent uretero-ureterostomy anterior to the inferior vena cava, and recovered well. Detailed evaluation for upper urinary tract is mandatory for high grade VUR, and Cohen technique should be avoided for VUR associated with RCU.